THE INFLUENCE OF SUNDANESE ZITHER (KACAPI) MUSIC THERAPY ON ANXIETY LEVELS IN PRE-CARDIAC CATHETERIZATION PATIENTS - Kristiana Prasetya Handayani; Andrew Johan; Chandra Bagus Ropyanto (Belitung Nursing Journal, 2018)
Background: Patients who will have cardiac catheterization mostly experience anxiety. Unresolved anxiety may have a harmful effect such as increasing frequency of heart, breathing and blood pressure as well as risks of complication. Music is considered effective in reducing anxiety. Objective: This study aims to examine the effect of Sundanese zither (kacapi) music therapy on anxiety level in pre-cardiac catheterization patients. Methods: This was a quasi-experimental study. Fifty-six respondents were selected using consecutive sampling technique, which 28 respondents assigned in the experiment group and control group. Anxiety was measured using Hamilton Anxiety rating Scale (HARS). Data were analyzed using Wilcoxon and Mann-Whitney test. Results: The results showed an average decrease in anxiety value in the experiment group of 10.28, and in the control group of 3.25. Mann-Whitney test results obtained p value <0.001, which indicated that there was a significant difference of mean decrease between the experiment group and the control group. Conclusion: This study proves that the intervention of Sundanese kacapi music significantly decreasing anxiety levels (p <0.001) in pre-cardiac catheterization patients. It is suggested that Sundanese kacapi music can be used as an alternative therapy in the independent nursing interventions.